Promoting Anthropology: Idle Thoughts from a Talking Head - McCracken, Grant (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1988)
In the last decade, Canadian anthropologists have evidenced new interest in the public promotion of their field and the broader dissemination of their research findings. The present paper is intended as a contribution to this vital issue. It reviews recent efforts to increase anthropology’s profile. It assesses the interaction of one anthropologist with the media. It hopes to encourage the media participation of anthropologists, and to suggest some of the strategies at their disposal.